Témoigner, dénoncer, révulser : dessins de haine, XXe-XXIe siècles - Gilbert Millat (Revue LISA)
The graphic satire label encompasses different trends in cartoon art, especially in Britain. Although the hate cartoon tradition actually represents a minority of published cartoons, it has been especially remarkable since the First World War. In various confrontational contexts, great artists feature in this tradition, ranging from Edmund Sullivan (1869-1933) to one of the leading cartoonists in the present generation, Steve Bell. This article focuses on aspects of the specific graphic rhetoric to be found in these images, and on their political impact as well as their echo in the media. The issues that cartoonists have recurringly been trying to bring up are also considered.